PLANT PROMOTING ACTIVITIES OF FUNGAL ENDOPHYTES ASSOCIATED WITH TOMATO ROOTS FROM CENTRAL HIMALAYA, INDIA AND THEIR INTERACTION WITH PIRIFORMOSPORA INDICA - NEHA CHADHA; RAM PRASAD; AJIT VARMA (International Journal of Pharma and Bio Sciences, 2015)
Endophytic fungi promote plant growth through the production of IAA, siderophore and phosphate solubilization. Out of thirty fungal endophytes isolated from tomato roots grown in a stressed, cold climate of Central Himalayan hills of district Pithoragarh, Uttarakhand, India twelve showed distinct morphological and study was undertaken, to understand the plant growth promoting properties possessed by these endophytes residing under stress environment. All the fungi showed the zone of phosphate solubilization, seven were positive for siderophore, four for HCN and three-showed ammonia production. IAA production was found maximum in Fusarium fusarioides. All the endophytic fungi showed remarkable phosphate solubilizing activity up to eight days with a decrease on the 10th day with maximum reporting from Trichoderma peudokoningii. All the isolates showed maximum siderophore production at 21th day after the inoculation. These isolated root endophytic fungi possess plant growth promoting properties and thus have a potential to be used for biofertilizer.